Analisis Wacana Perilaku Homoseksual pada Serial Animasi “The Loud House” - Syabila Aprila Zakaria; Deden Mauli Darajat (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
. Public understanding of discourse embedded in children’s animated film scripts and their underlying purposes remains limited, resulting in low audience awareness of the implicit messages conveyed in meaning-laden children’s animations. The Loud House, broadcast by the children’s television network Nickelodeon, presents a relatively controversial theme by incorporating homosexual discourse, which is perceived as deviant behavior by certain segments of society. Based on this premise, this study examines the process through which homosexual behavior discourse is conveyed in The Loud House, addressing the research question: How is the discourse of homosexual behavior in The Loud House constructed in terms of textual messages, social cognition, and social context based on Teun A. Van Dijk’s discourse analysis framework?* This research adopts a qualitative approach using Van Dijk’s critical discourse analysis, which encompasses three analytical dimensions: text, social cognition, and social context. The findings indicate that homosexual discourse is represented through two supporting characters, Harold and Howard, depicted as a same-sex couple who adopt a young boy. These homosexual characters are deliberately framed with a positive image as caring and affectionate parents, comparable to the portrayal of heterosexual parents.